Pengaruh Bantuan Langsung Tunai Dana Desa dan Kemandirian Desa di Masa Pandemi terhadap Kemiskinan Desa di Indonesia - Gema Otheliansyah; Riedho Hizwar (Direktorat Sistem Perbendaharaan, 2023)
Besides its effect on public health, Covid-19 also affects social and economic aspects in citizen life. To minimize these impacts, the government has distributed The Village Fund Direct Cash Assistance (BLT DD) as the social safety net program by giving cash to the poor and the underprivileged families in the village. This research aims to determine the effect of BLT DD and the number of independence village as variable to village poverty in 33 Provinces in Indonesia. This study is quantitative research using data panel regression. The result shows that BLT DD and increase on the number of independence village had negative impact on village poverty in 33 Provinces in Indonesia.